Resilience Amidst a Challenging Environment : Cambodia Economic Update, September 2013 - World Bank (Washington, DC, 2014)
According to the June 2013 global economic prospects, the global economic environment remains fragile, although the balance of risks is now less skewed to the downside than it has been in recent years. The US has been signaling an exit from quantitative easing. Developing country currencies have come under pressure, and their interest rates have been on the rise, contributing to inflation and weaker growth. This may complicate in particular those economies that have seen big increases in credit during the period when interest rates were low, or where current account and government deficits are high. Developing economies remain the main driver of global growth, but their output has slowed compared with the pre-crisis period. The Cambodian economy remains robust amidst the challenging global economic environment, and prospects for meeting the growth projection of 7 percent in 2013 appear favorable. In sum, the key messages include: (a) sustain robust growth by promoting diversification and enhancing competitiveness; (b) maintain banking and financial stability with effective supervision; and (c) improve fiscal management by increasing revenue and more efficient spending.